Hate speech - Carlson, Caitlin Ring (MIT Press essential knowledge series, 2021)
An investigation of hate speech: legal approaches, current controversies, and suggestions for limiting its spread. Hate speech can happen anywhere--in Charlottesville, Virginia, where young men in khakis shouted, "Jews will not replace us"; in Myanmar, where the military used Facebook to target the Muslim Rohingya; in Capetown, South Africa, where a pastor called on ISIS to rid South Africa of the "homosexual curse." In person or online, people wield language to attack others for their race, national origin, religion, gender, gender identity, sexual orientation, age, disability, or other aspects of identity. This volume in the MIT Press Essential Knowledge series examines hate speech: what it is, and is not; its history; and efforts to address it.